Оцінка потенціалу енергозбереження при застосуванні рекуперації енергії на моторвагонному електрорухомого складу для приміських перевезень - Буряковський, Сергій Геннадійович; Овер'янова, Лілія Вікторівна; Нещерет, Володимир Олексійович; Іванов, Костянтин Ігорович (Національний технічний університет "Харківський політехнічний інститут", 2023)
Вирішено серію тягових задач для ділянки Харків-Пасажирський – Мерефа при русі базової секції електрорухомого складу. Встановлено, що коефіцієнт рекуперації для секції змінюється у діапазоні 0,26 – 0,47 і залежить від допустимої швидкості руху. Визначено, що потужність бортового накопичувача енергії має відповідати нормативній потужності тягового електроприводу, яка дорівнює 1200 кВт. Енергоємність накопичувача, який працює у режимі акумулювання енергії та живленні тягового електроприводу, становить 8,2 кВт·год.

The purpose of the article is to evaluate the potential of energy saving when using conventional regenerative braking or accumulation in an on-board energy storage on rolling stock for suburban rail. A mathematical model has been developed that describes the movement of the two-car base unit on the railroad segment and takes into account the terms of the theory of locomotive traction, to determine theoretical indicators for conventional regenerative braking and on-board accumulation. A series of traction problems were solved for the movement of the two-car base unit on the Kharkiv-Pasajyrskyi – Merefa railroad segment. To evaluate the efficiency of conventional regenerative braking, the recuperation coefficient was calculated, which varies in the range of 0.26-0.47. The permissible speed has the most significant effect on the recuperation coefficient. It was determined that the power of the on-board energy storage must correspond to the normative power of the traction electric drive, which for the researched base unit is equal to 1200 kW. The energy capacity of the on-board energy storage, which operates in the electrodynamics braking mode, accumulates energy and then feeds the traction electric drive during acceleration, can be taken equal to 8.2 kWh. The technical parameters of the energy storage system must be sufficient to provide unrestricted energy flows between the storage and the traction drive.
Energy saving potential evaluation for the regenerative braking applications on the rolling stock for suburban rail
Keywords: електрорухомий склад; енергоефективність; тягова задача; моделювання; рекуперація; накопичувач енергії; electric rolling stock; energy efficiency; traction problem; modeling; recuperation; energy storage